2018
DOI: 10.1021/acs.organomet.8b00418
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Impact of High-Oxidation State Main-Group Metal and Ligands on Alkane C–H Activation and Functionalization Reactions

Abstract: High-oxidation state main-group metal complexes are potential alternatives to transition metals for electrophilic alkane C−H functionalization reactions. However, there is little known about how selection of the p-block, main-group metal and ligand impact alkane C−H activation and functionalization thermodynamics and reactivity. This work reports density functional theory calculations used to determine qualitative and quantitative features of C−H activation and metal-methyl functionalization energy landscapes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 116 publications
0
9
0
Order By: Relevance
“…The transition state (TS D ‡ ) bearing a C−H activated CH 4 was obtained by the QST3 method and found to have a sixmembered ring consisting of an activated CH 4 , the Au III center, and two oxygen atoms in the CF 3 SO 3 − ligand. This transition state has a free energy barrier of 26.7 kcal/mol from structure B. Six-membered metal cycle with activated Csp3-H structures have also been reported on metal atoms such as Pt, 79 Ir, 18 and Ti 21,80 H-bonding effect is considered to be minor without affecting the relative energies of the species in the reaction profiles. In addition to the five-coordinated structure, as described in Figure 3, monovalent cation structures in the C−H activation process were all calculated by DFT calculation.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…The transition state (TS D ‡ ) bearing a C−H activated CH 4 was obtained by the QST3 method and found to have a sixmembered ring consisting of an activated CH 4 , the Au III center, and two oxygen atoms in the CF 3 SO 3 − ligand. This transition state has a free energy barrier of 26.7 kcal/mol from structure B. Six-membered metal cycle with activated Csp3-H structures have also been reported on metal atoms such as Pt, 79 Ir, 18 and Ti 21,80 H-bonding effect is considered to be minor without affecting the relative energies of the species in the reaction profiles. In addition to the five-coordinated structure, as described in Figure 3, monovalent cation structures in the C−H activation process were all calculated by DFT calculation.…”
Section: Methodsmentioning
confidence: 89%
“…5−14 A large number of works on selective CH 4 oxidation have been focused on metal complexes, including precious metals such as Pt II , 15 Pd II , 16 Au III/I , 17 and Ir III18 and main-group metals such as Hg II , 19 Sb V , 20 In III , Sn IV , Ti II , and Pb IV in strongly acidic media. 21 A landmark work by Periana et al 14 showed the conversion of CH 4 to methyl bisulfate, (CH 3 )HSO 4 , as a primary product that was subsequently worked up by hydrolysis to produce CH 3 OH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results reflected that of a recent publication on the mechanism of methane activation by main group trifluoroacetates, and readers are directed there for a more in-depth discussion of the electronic structure of 2 with respect to its reactivity. 49 During our early attempts to structurally characterize 1 F and 2 F , we obtained crystals of other compounds that hinted at the rich structural diversity available to tin trifluoroacetates. The cagelike cluster hexakis[tin(II) bis(trifluoroacetate) trimethylphosphine]…”
mentioning
confidence: 99%
“…Our results reflected that of a recent publication on the mechanism of methane activation by main group trifluoroacetates, and readers are directed there for a more in-depth discussion of the electronic structure of 2 with respect to its reactivity. 49 During our early attempts to structurally characterize 1 F and 2 F , we obtained crystals of other compounds that hinted at the rich structural diversity available to tin trifluoroacetates. The cagelike cluster hexakis[tin(II) bis(trifluoroacetate) trimethylphosphine] [(1 ←PMe ) ] was obtained by slow cooling of a toluene solution of 1 F and a slight excess of PMe 3 .…”
mentioning
confidence: 99%